Subthreshold micropulse yellow laser treatment for nonresolving central serous chorioretinopathy - Abd Elhamid AH (Dove Medical Press, 2015)
Ahmed Hosni Abd ElhamidDepartment of Ophthalmology, Ain Shams University, Cairo, EgyptPurpose: To report the efficacy and safety of micropulse 577 nm yellow laser in the treatment of nonresolving central serous chorioretinopathy (CSC) cases.Patients and methods: The study included 15 eyes with nonresolving CSC lasting more than 3 months. All the patients were subjected to complete ophthalmic examination, in addition to contrast sensitivity measurement, fundus fluorescein angiography, and optical coherence tomography. All eyes were subjected to 577 nm subthreshold micropulse laser treatment, using the IQ 577 device, and followed up after 4 weeks, 2 months, 3 months, and 6 months. The outcome measures were change in best-corrected visual acuity, contrast sensitivity, subretinal fluid height, and change in macular thickness measured by optical coherence tomography.Results: The average age of the patients was 36.4 years; eleven were males and four were females. Average duration of the leakage was 4.6 months. The mean best-corrected visual acuity measured 6 months after laser treatment was 0.85±0.097, in comparison to 0.67±0.097 before laser treatment (statistically significant [SS], P<0.05). The mean central macular thickness before laser was 389.6±46.4 µm, in comparison to 263.6±24 µm after 6 months (SS, P<0.05). The mean post-laser log contrast sensitivity measured using the Pelli–Robson contrast sensitivity chart was 1.73±0.14, while the initial log contrast sensitivity was 1.48±0.28 (SS, P<0.05).Conclusion: Subthreshold micropulse laser treatment is an effective and safe treatment option for patients with nonresolving CSC.Keywords: subthreshold micropulse laser, central muscular thickness, best corrected visual acuity, optical coherence tomography